Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.biochi.2012.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosyl-DNA phosphodiesterase 1 initiates repair of apurinic/apyrimidinic sites

Abstract: Tyrosyl-DNA phosphodiesterase 1 (Tdp1) catalyzes the hydrolysis of the phosphodiester linkage between the DNA 3′ phosphate and a tyrosine residue as well as a variety of other DNA 3′ damaged termini. Recently we have shown that Tdp1 can liberate the 3′ DNA phosphate termini from apurinic/apyrimidinic (AP) sites. Here, we found that Tdp1 is more active in the cleavage of the AP sites inside bubble-DNA structure in comparison to ssDNA containing AP site. Furthermore, Tdp1 hydrolyzes AP sites opposite to bulky fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 26 publications
(11 reference statements)
0
33
0
Order By: Relevance
“…To confirm that TDP1 catalytic activity is required for cellular tolerance to ABC, we prepared two mutant TDP1 transgenes [ H263A and H493R ( 13 , 24 )] and a wild-type TDP1 transgene ( 25 ) and ectopically expressed them in MT-2 cells to generate MT-2/ TDP1 H263A , MT-2/ TDP1 H493R , and MT-2/ TDP1 WT cells, respectively (fig. S6, A to C).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm that TDP1 catalytic activity is required for cellular tolerance to ABC, we prepared two mutant TDP1 transgenes [ H263A and H493R ( 13 , 24 )] and a wild-type TDP1 transgene ( 25 ) and ectopically expressed them in MT-2 cells to generate MT-2/ TDP1 H263A , MT-2/ TDP1 H493R , and MT-2/ TDP1 WT cells, respectively (fig. S6, A to C).…”
Section: Resultsmentioning
confidence: 99%
“…SVPDE1 (snake venom phosphodiesterase 1) from Crotalus adamanteus was from Worthington (Biochemical Corporation). Human tyrosyl-DNA phosphodiesterase 1 (Tdp1) was purified as described previously (44). The purified human Nudix (nucleoside diphosphate-linked moiety X)-type motif 16 (NUDT16) protein was kindly provided by Dr Ivan Ahel (University of Oxford, U.K.).…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant human TDP1 and PARP1 were expressed in the Escherichia coli system [strain BL21 DE3 (pLys E)] and purified as described previously ([ 7 , 19 ] and [ 20 ] respectively). The recombinant plasmid pET 16B-TDP1 was kindly provided by Dr K.W.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have shown that human tyrosyl–DNA phosphodiesterase 1 (TDP1) cleaves AP sites with the formation of the 3′- and 5′-phosphate termini, suggesting a novel AP-endonuclese independent pathway of AP-site processing [ 6 9 ] that can be involved in the repair of AP sites clustered with bulky DNA lesions [ 7 ]. The unique enzymatic activity of TDP1 removes the covalently-linked adducts of DNA topoisomerase I (Top1) from the DNA 3′-end [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%